Pengaruh Komitmen Organisasi Terhadap Kinerja Karyawan di PT. X - Ardian Syach Mulyawardhana; Netty Merdiaty (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2025)
Every organization has the same goal, which is to increase employee productivity, an important thing that affects employee productivity is employee performance. Performance is the behavior shown by employees while working, which contributes to the achievement of organizational goals. Organizational commitment is one of the important factors to improve employee performance in carrying out the assigned work tasks. The purpose of this study is to determine whether there is an influence of organizational commitment on employee performance at PT. X. The method used in this study is regression analysis to see the effect of the independent variable on the dependent variable under study and the data analysis process using IBM SPSS 27 software. The sample in this study amounted to 120 respondents and was selected using purposive sampling technique. The results in this study get a linear regression coefficient value of 0.014 with a significance value of 0.204 or (ρ)> 0.05 which shows the effect of organizational commitment on employee performance is 1.4% and organizational commitment has no significant effect on employee performance.